Fatigue reliability theory-based optimal design of wire ropes on test platforms for FAST actuators. Issue 3 (12th October 2015) - Zhu, Ming; Wang, QiMing; Yang, Lei; Lei, Zheng; Wang, Yong; Wu, Mingchang
Abstract : Purpose: – Three test platforms for long-term continuous loading are adopted to test the actuator prototypes of the 500-meter aperture spherical radio telescope (FAST). However, the wire ropes that are the key components of these platforms often break during testing. The purpose of this paper is to present an effective dimension design method for these wire ropes. This method is based on fatigue reliability theory. Design/methodology/approach: – Three types of stresses are introduced into the total stress model of the wire rope according to the complicated stress conditions. The fatigue strength of the ropes is also discussed in this paper. Then, the total stress model and the results of fatigue strength analysis are applied to set the optimization function for these wire ropes. Subsequently, this optimization function is used to calculate the reliability of previously developed wire ropes in relation to the actuator test platform. Findings: – The wire rope is unreliable, which is a finding that corresponds to those of previous tests. Upon drawing the optimal curve from the optimization function (whose optimal objective is the wire diameter), a wire rope is optimized for the FAST actuator test platforms. Finally, this optimized rope is used on the new actuator test platform. No fracture phenomenon has been detected in tests conducted over the past six months. Originality/value: – The fatigue reliability theory-based optimization function for wire ropes can be adopted for the universal dimension design of other wire ropes.